PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB GOOGLE SITES PADA PEMBELAJARAN IPA SEKOLAH DASAR MATERI SIFAT-SIFAT CAHAYA KELAS V - Ratno, Suyit; Sijabat, Melisa Pratiwi; Sitorus, Lestari; Salsabilla, Salsabilla; Batubara, Alfredo; Nasution, Nia Afrilda; Syazidah, Hanna (Universitas Negeri Medan, 2023)
This research aims to produce a product in the form of learning media, namely web-based learning media with Google Sites as a site creation tool. A validation test was carried out to assess the feasibility and quality of the Google Sites web-based learning media for grade V elementary school science learning. This type of research is development research (R&D) with the ADDIE model, consisting of five steps: analysis, design, development, implementation and evaluation. Data collection techniques involve observation or observations, and questionnaires. The results of the validation test by two validators, namely the media expert validator obtained an average percentage value of 67.5%, interpreted into the feasible category, and the material expert validator obtained an average percentage value of 100% in the very feasible category. Students' responses to the media achieved 100% results in the very appropriate category. And the teacher's response to learning media received a percentage score of 100% in the very appropriate category. Based on the data that has been obtained, it can be concluded that the Google Sites web-based learning media for grade V elementary school science learning is suitable for use in learning activities.